The Johannine Prologue and its Resonances - Porter, Stanley E.,; Yoon, David I., (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
The Prologue to John's Gospel has been an enigmatic object of inquiry in the history of biblical scholarship. This volume reengages readers with thirteen essays from various perspectives on the Prologue. These perspectives include source oriented approaches, form oriented approaches, functional approaches, and alternative non-traditional approaches. This book attempts to pave new paths to understanding the Prologue and cause readers to think more deeply about the beginning of John's Gospel.